Protein adjustments during temperature stress - Ames, D.R. (Kansas State University. Agricultural Experiment Station, 2011)
Adjusting feedlot rations to match the thermal environment can reduce costs of gains. Adjusting protein content of rations does not change average daily gain but it improves protein efficiency.
Keywords: Beef; Protein; Temperature; Rations